Towards a Transformative Framework for AR Learning and Instruction Through the Lenses of Research and Practice: An Interdisciplinary Community Workshop - Krüger, Jule M.; Buchner, Josef; Altmeyer, Kristin; Georgiou, Yiannis; Hoyer, Christoph; Palzer, Kevin; Kozlova, Zoya; Malone, Sarah; Garzon Alvarez, Juan Fernando; Hofer, Sarah; Bodemer, Daniel (My University, 2025)
The proposal describes an interdisciplinary community workshop that is executed at iLRN2025. The goal of the workshop is to gather insights from the community concerning their research on and use of AR in education. It is a first step to build a foundation for a broader project creating an evidence- and experience-based framework for the transformation of research on and practice with AR for learning and instruction. In this workshop, members of the iLRN community will have the opportunity to share their personal experiences with AR in education, explore use cases of AR including the potentials of novel, innovative technologies, and connect these with pedagogical theories and frameworks. Through small group brainstorming and discussion sessions, a participatory approach will be adopted with the goal of collecting various perspectives and experiences. The multi- and interdisciplinary perspectives of researchers and practitioners from various fields (e.g., teachers, instructional designers, learning facilitators, museum curators) will be combined in this workshop. With the interdisciplinary insights and novel connections from the workshop a starting point will be formed for the co-creation of a theory-based and practice-inspired framework for the implementation of AR technology in instructional settings.
Keywords: Augmented Reality; Education; Co-Creation; Transformative Framework